Revision of the Palearctic species of Macroglenes Westwood (Hymenoptera: Pteromalidae) - Mitroiu, Mircea-Dan (Zootaxa, 2010)
The Palearctic species of Macroglenes Westwood (Hymenoptera: Pteromalidae) are revised. A brief diagnosis is given for each species and distribution and hosts are summarized. Twenty species are regarded as valid, including eight described as new: M. caudatus sp. nov., M. gibsoni sp. nov., M. hokkaidensis sp. nov., M. incisiclypeatus sp. nov., M. japonicus sp. nov., M. noyesi sp. nov., M. samurai sp. nov., and M. zdeneki sp. nov. Macroglenes nigroclypeatus Amerling & Kirchner, 1860 is treated as nomen dubium. Stenophrus Förster is regarded as a synonym of Macroglenes Westwood, syn. nov. Consequently, Calypso Haliday and Euryophrys Förster are treated as synonyms of Macroglenes Westwood, syn. nov. Another two new synonyms and two new combinations are proposed: M. chalybeus Haliday = M. rasnitsyni (Dzhanokmen), syn. nov., M. penetrans (Kirby) = M. decipiens (Graham), syn. nov., Stenophrus compressus Förster = Macroglenes compressus (Förster), comb. nov., and Pirene yuasai Ishii = Macroglenes yuasai (Ishii), comb. nov. New distributional data are given for eight species. The association between M. gramineus (Haliday) and Contarinia tritici (Kirby) (Diptera: Cecidomyiidae) is published for the first time, as well as several parasitoid-plant associations.